Burden among Primary caregivers and its association with severity of Disability in patients with Schizophrenia: A Cross-sectional study - Shobitha George; A John Dinesh; MA Melody (Journal of Family Medicine and Primary Care)
Background: Caregivers of individuals with schizophrenia play a crucial role in providing support, but they frequently experience significant levels of stress and burden due to the demanding nature of caregiving responsibilities. Objectives: To estimate the magnitude of caregiver burden in the primary caregivers of patients with schizophrenia; and to find out the association between severity of disability in patients with schizophrenia and caregiver burden. Methods: This was a hospital-based analytical cross-sectional study involving patients diagnosed with Schizophrenia and their primary caregivers (n = 72) attending the Psychiatry, OPD of a tertiary healthcare facility in Puducherry. PANSS, IDEAS, and BAS were used to assess the severity of illness and burden among primary caregivers, respectively. Results: The mean ages of schizophrenia patients and primary caregivers were 39.2 years and 43.1 years, respectively. The proportion of females among patients was 54.2% and that among primary caregivers was 65.3%. The mean (SD) IDEAS global disability score among people with schizophrenia was 7.1 ± 2.6, while the total PANSS score was 51.8 ± 11.4. The mean (SD) burden assessment schedule scores among caregivers were 72.9 ± 13.2. Caregiver burden was notably higher among those over 40 yrs, living in urban areas, literate, employed, of lower or middle socioeconomic status, and from nuclear families (P < 0.05). However, gender, religion, marital status, and substance use did not affect burden (P > 0.05). Caregivers experiencing burden had patients with higher illness severity and disability, as indicated by elevated PANSS and IDEAS scores (P < 0.05). Moreover, caregiver age (r = 0.147), patient illness severity (r = 0.261), treatment duration (r = 0.351), and various aspects of patient disability (r = 0.383) showed positive correlations with caregiver burden. Conclusion: The caregiver burden is significantly correlated with patient illness severity, disability, and treatment duration, particularly affecting older caregivers and those from specific socioeconomic backgrounds. The findings underscore the considerable challenges faced by caregivers in supporting individuals with schizophrenia and highlight the need for targeted interventions and support services to reduce caregiver burden and enhance patient outcomes.